Assessment of the roles of librarians in altmetrics: evidence from two Nigerian universities (2022)
This study assessed the roles of librarians in altmetric with evidence from two Nigerian university libraries (University Of Ibadan and Obafemi Awolowo University) to embrace ICT. Survey research design was employed in carrying out the study. Total enumeration technique was used to cover the academic librarians. The study further made use of questionnaire and focus group discussion (FGD) with four key informants. The findings from the thematic analysis showed that large numbers of Nigerian academic librarians are not aware of the altmetrics or still mistaken the tool for citations and journal impact factor. The need to expose academic librarians to periodic training on the concept, importance and advantages which will in turn facilitate the use of the tools to assist the scientists/researchers in creating societal impact with their research outcomes were suggested.